Study on the Effect of High-Temperature Heat Treatment on the Microscopic Pore Structure and Mechanical Properties of Tight Sandstone. (5th April 2021) - Dou, Liangbin; Shu, Guanli; Gao, Hui; Bao, Jinqing; Wang, Rui
Abstract : The investigation of changes in physical properties, mechanical properties, and microscopic pore structure characteristics of tight sandstone after high-temperature heat treatment provides a theoretical basis for plugging removal and stimulation techniques, such as high energy gas fracturing and explosive fracturing. In this study, core samples, taken from tight sandstone reservoirs of the Yanchang Formation in the Ordos Basin, were first heated to different temperatures (25-800°C) and then cooled separately by two distinct cooling methods—synthetic formation water cooling and natural cooling. The variations of wave velocity, permeability, tensile strength, uniaxial compressive strength, and microscopic pore structure of the core samples were analyzed. Experimental results demonstrate that, with the rise of heat treatment temperature, the wave velocity and tensile strength of tight sandstone decrease nonlinearly, yet its permeability increases nonlinearly. The tight sandstone's peak strength and elastic modulus exhibit a trend of the first climbing and then declining sharply with increasing temperature. After being treated by heat at different temperatures, the number of small pores varies little, but the number of large pores increases obviously. Compared to natural cooling, the values of physical and mechanical properties of core samples treated by synthetic formation water cooling are apparently smaller, whereas the size and number of pores are greater. It can be explained that water cooling brings about a dramatic reduction of tight sandstone's surface temperature, generating additional thermal stress and intensifying internal damage to the core. For different cooling methods, the higher the core temperature before cooling, the greater the thermal stress and the degree of damage caused during the cooling process. By taking into consideration of changes in physical properties, mechanical properties, and microscopic pore structure characteristics, the threshold temperature of tight sandstone is estimated in the range of 400-600°C.